2018
DOI: 10.5897/jaerd2018.0967
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm Demonstration of Improved Varieties of Faba bean (Vicia fabaL.) in Gemechis, Chiro and Tullo Districts of West Hararghe Zone, Oromia National Regional State of Ethiopia

Abstract: In west hararghe Zone there was no improved technology of faba bean done on farmer's field and no high yield variety and drought resistant variety demonstrated to reach farmers widely in future.The experiment was carried out in Gemechis,Chiro and Tulo districts of West Harerghe Zone with the objectives of enhancing production and productivity of faba bean on farmers` fields, and to improve linkage among stakeholders and create awareness on improved faba bean varieties. Three kebeles were selected purposively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Relatively, Hachalu had better plant stands as compared to Didia and the locals. The result is consistent with the findings [13] that indicate the Hachalu variety ranked first in terms of grain yield, disease resistance, and seed color. In the production season, there was also high frost damage at grain grain-filling stage of the crop in north Shewa which resulted in poor crop harvest.…”
Section: The Yield Performance Of Improved Faba Bean Varietiessupporting
confidence: 92%
“…Relatively, Hachalu had better plant stands as compared to Didia and the locals. The result is consistent with the findings [13] that indicate the Hachalu variety ranked first in terms of grain yield, disease resistance, and seed color. In the production season, there was also high frost damage at grain grain-filling stage of the crop in north Shewa which resulted in poor crop harvest.…”
Section: The Yield Performance Of Improved Faba Bean Varietiessupporting
confidence: 92%
“…Faba beans have several advantages in the economic life of the agricultural communities of the country's highlands (Fekede et al, 2018). Similarly, they reported that besides its important role in soil fertility maintenance, it is used as food, feed for livestock, and means of income for farmers.…”
Section: Introductionmentioning
confidence: 99%